Leksikon Khas Ramadan dalam Masyarakat Muslim Indonesia di Media Sosial: Kajian Antropolinguistik - Gadis Artika; Dian Aurelia Febrina; Nailah Azura Sandi; Ida Basaria (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aims to identify and analyze Ramadan-specific lexicons used by Indonesian Muslim communities on social media, as well as to describe the cultural meanings embedded within them. The study employs an anthropolinguistic approach with a descriptive qualitative method. Data were collected through observation and note-taking techniques from three social media platforms X (Twitter), TikTok, and Instagram during the Ramadan 1446 H/2025 period. A total of 32 Ramadan-specific lexicons were identified and classified into three categories: greetings and expressions (12 items), worship-related lexicons (10 items), and culinary lexicons (10 items). The findings reveal that Ramadan lexicons circulating on social media reflect a blend of Islamic religious values, local Indonesian cultural traditions, and the influence of digital globalization. The hybrid nature of the language used — including code-mixing between Indonesian, Arabic, and English — illustrates the dynamic cultural identity of contemporary Indonesian Muslims. Ultimately, this study affirms that language is a living mirror of culture, one that continues to evolve alongside social and technological change.